Comparative Study on the Adsorption of [AuCl4]– onto Salicylic Acid and Gallic Acid Modified Magnetite Particles - Maya Rahmayanti; Sri Juari Santosa; Sutarno Sutarno (Indonesian Journal of Chemistry, 2016)
Salicylic acid-modified magnetite (Mag-SA) and gallic acid-modified magnetite (Mag-GA) particles were prepared by co-precipitation procedure. Characterization results showed the interaction that occurs between the surface of magnetite with salicylic acid (Mag-SA) and gallic acid (Mag-GA) was through hydrogen bonding. Adsorption of [AuCl4]– onto Mag-SA and Mag-GA surfaces as a function of initial pH, contact time, and initial concentration of the [AuCl4]– solution were comparatively investigated. Result showed that the optimum adsorption of [AuCl4]– onto Mag-SA or Mag-GA was found at pH 3. The adsorption process were found to allow the pseudo-second order equation, both for Mag-SA and Mag-GA. The parameters in isotherm adsorption equations conformed to the Langmuir and Freundlich isotherms very well for Mag-GA, but for Mag-SA, only conformed to the Langmuir isotherm very well. The result of this study demonstrate that the ability Mag-GA to adsorb [AuCl4]– higher than Mag-SA.